2005
DOI: 10.1115/1.1934056
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Flow Structure in Arterial Bypass Anastomosis

Abstract: The fluid flow through a stenosed artery and its bypass graft in an anastomosis can substantially influence the outcome of bypass surgery. To help improve our understanding of this and related issues, the steady Navier-Stokes flows are computed in an idealized arterial bypass system with partially occluded host artery. Both the residual flow issued from the stenosis--which is potentially important at an earlier stage after grafting--and the complex flow structure induced by the bypass graft are investigated. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…CFD has also been employed to investigate anastomotic regions of bypass grafts. 4,5,25,31,38 Although these studies were motivated similarly by pathological responses observed in particular at the distal anastomosis of arterial bypass grafts, the simulations focussed at arterial blood flow; as such they did not deal with the fluid mechanics of AV connections.…”
Section: Introductionmentioning
confidence: 99%
“…CFD has also been employed to investigate anastomotic regions of bypass grafts. 4,5,25,31,38 Although these studies were motivated similarly by pathological responses observed in particular at the distal anastomosis of arterial bypass grafts, the simulations focussed at arterial blood flow; as such they did not deal with the fluid mechanics of AV connections.…”
Section: Introductionmentioning
confidence: 99%
“…The posterior mean and covariance can be computed as (6) and (7) where is the correlation matrix computed using the training points; the th element of this matrix is computed as . is the correlation between the new point and the training points and .…”
Section: Bayesian Modelingmentioning
confidence: 99%
“…In the case of grafting, graft failure may occur due to the compliance mismatch at the junction between the native vessel and the graft [5]. In addition, there is some evidence to suggest that the geometry of the arterial bypass can significantly influence the postoperative haemodynamic environment [6], [7]. Hence, selection of an optimal shape and a suitable material for a bypass graft could play a critical role in inhibiting mechanical failure.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the use of computational techniques in fluid dynamics to analyze physiological flows involving blood is an area of intensive research (Maurits et al, 2007;Pedrizzetti and Perktold, 2003;Sousa et al, 2012;Su et al, 2005). Blood flow is normally laminar but the periodic unsteadiness or pulsatile nature of the flow makes possible the transition to turbulence when the artery diameter decreases and velocities increase.…”
Section: Introductionmentioning
confidence: 99%